2000
DOI: 10.1001/archinte.160.13.1947
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Weight Loss Reduce Blood Pressure in Men and Women With Mild Hypertension

Abstract: Background: Lifestyle modifications have been recommended as the initial treatment strategy for lowering high blood pressure (BP). However, evidence for the efficacy of exercise and weight loss in the management of high BP remains controversial. Methods:One hundred thirty-three sedentary, overweight men and women with unmedicated high normal BP or stage 1 to 2 hypertension were randomly assigned to aerobic exercise only; a behavioral weight management program, including exercise; or a waiting list control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
111
0
8

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 240 publications
(124 citation statements)
references
References 46 publications
5
111
0
8
Order By: Relevance
“…However, studies assessing the effect of weight loss on BP have frequently failed to take into account the effect of continued weight loss or negative energy balance on BP. [18][19][20] Actually there are quite a few studies that should have assessed the effects of weight maintenance after marked weight loss on BP. The Swedish Obesity Study showed that after marked surgically induced weight loss there was no improvement in the long-term frequency of hypertension, 21 which are in accordance with our study 22 in which dietinduced weight loss in abdominally obese subjects decreased ambulatory BP levels after weight loss, but during weight maintenance the BP returned to pretreatment levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies assessing the effect of weight loss on BP have frequently failed to take into account the effect of continued weight loss or negative energy balance on BP. [18][19][20] Actually there are quite a few studies that should have assessed the effects of weight maintenance after marked weight loss on BP. The Swedish Obesity Study showed that after marked surgically induced weight loss there was no improvement in the long-term frequency of hypertension, 21 which are in accordance with our study 22 in which dietinduced weight loss in abdominally obese subjects decreased ambulatory BP levels after weight loss, but during weight maintenance the BP returned to pretreatment levels.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a large meta-analysis (54), which reported an overall beneficial effect of chronic exercise on blood pressure, found that the average weight loss across the reviewed trials was largely inconsequential (-1.2 kg). Nevertheless, some studies report that individuals who become active and also lose a significant amount of weight (-7.9 kg), in comparison with those who lose minimal weight (-1.8 kg), show greater reductions in systolic and diastolic blood pressure (-7 mmHg and -5 mmHg versus -4 mmHg and -4 mmHg, respectively) (55).…”
Section: Exercise-induced Reduction In Cardiometabolic Risk Factors Wmentioning
confidence: 99%
“…The lipid improvements independent of significant weight reduction may also be mediated by improvements in body composition, such as reductions in visceral fat (60), but apparently are not due to improvements in CRF (51). Lastly, it appears that physical activity and weight loss may have independent effects on blood pressure, because reductions in blood pressure are significantly related to training-induced improvements in CRF (54), as well as the magnitude of weight loss (55).…”
Section: Exercise-induced Reduction In Cardiometabolic Risk Factors Wmentioning
confidence: 99%
“…This study represents a secondary analysis of a previously reported clinical trial examining the effects of exercise and weight loss in a sample of patients with high blood pressure [34]. Briefly, participants had unmedicated high normal BP or stage 1 to 2 hypertension and were sedentary, overweight or obese, and were at least 29 years old.…”
Section: Participantsmentioning
confidence: 99%